The complete mitochondrial genome of the deep-sea amphipod Eurythenes magellanicus (Crustacea: Amphipoda: Lysianassidae) - Jun-yuan Li; Yan-wen Liao; Jun Li; Li-sheng He (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of the deep sea amphipod Eurythenes magellanicus was determined in this paper. This molecular was 14,988 bp in length, and contained the typical 13 protein coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and one control region (CR). The gene order of E. magellanicus was identical to that from E. maldoror, a deep sea amphipod inhabiting in a deeper habitat than E. magellanicus. A maximum-likelihood tree based on the 13 PCGs from 25 amphipods indicated that E. magellanicus and E. maldoror were closely related and the origin of deep sea amphipods was not monophyletic.